Energy dependence of western Europe: The rise and fall - Glamotchak Marina (Međunarodni Problemi, 2015)
The relationship between energy sources import and export is placed in the centre of energy security analysis. The issue of the future of Europe is becoming increasingly important with the depth of the economic crisis that started in 2008. In addition to a continuous growth in the number of the unemployed, the crisis particularly emphasizes the chronic level of energy dependence. The energy saving measures (energy efficiency), diversification of sources (stability of supply), and the creation of substitutes in renewable energy (energy transition), interwin with administrative measures and form the response of European countries to the growing energy dependence. At the same time, although facing the threatening warming (or cooling) of the Earth, Europe, as a big advocate of reducing CO2 remains passively dependent on NATO policy in the field of defence in the context of energy dependence. However, for the first time after many decades, Europe and America do not have the same energy, and consequently geo-strategic objective: the United States has become energy independent, while Europe is chronically energy dependent. Preservation of the environment and the fight against climate deregulation becomes a crucial energy security domain.